Hiding Files in Image Files Using the Steganography Method - Irawan, Dedi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2020)
The need for communication in the digital era at this time makes the insertion of information applicable to digital files / media such as images, video, audio and text. Steganography inserts a secret message in a file / media without anyone realizing that the media has a secret message. Steganography (information hiding) is a technique to hide secret messages on a media host or also called a media cover. Steganography comes from Greek which means